Odpowiedzi

2009-09-27T19:30:03+02:00
Wykonaj mnożenia;
(x-1)(x+3) =x²+3x-x-3=x²+2x-3
(2a+3)(4-3a)=8a-6a²+12-9a=-6a²+12-a
z(y+7)(2y-1)=z(2y²-y+14y-7)=2y²z-yz+14yz-7z=2y²z+13yz-7z

Jakie wyrażenia nalezy wpisać w nawiasach?
4x+2=2(.2x+1......)
6a4+5a=a(.6a³+5.....)
6t³-2t=2t(.3t²-1...)
2009-09-27T19:31:08+02:00
Wykonaj mnożenia;
(x-1)(x+3) =x²+3x-x-3=x²+2x-3
(2a+3)(4-3a)=8a-6a²+12-9a=-6a²-a+12
z(y+7)(2y-1)=z(2y²-y+14y-7)=z(2y²+13y-7)=(2y²z+13yz-7z)


Jakie wyrażenia nalezy wpisać w nawiasach?
4x+2=2(2x+1)
6a4+5a=a(6a³+5)
6t³-2t=2t(3t²-1)
2009-09-27T19:44:28+02:00
Wykonaj mnożenia;
(x-1)(x+3)=x²+3x-x-3= x²+2x-3

(2a+3)(4-3a)= 8a-6a²+12-9a=-6a²-a+12

z(y+7)(2y-1)=z(2y²-y+14y-7)=2y²z+13yz-7z

Jakie wyrażenia nalezy wpisać w nawiasach?
4x+2=2(2x+1)
6a4+5a=a(6a³+5)
6t³-2t=2t(3t²-1)